A liver health hui: hepatitis C knowledge and associated risk factors in New Zealand gang members and their families. Issue 8 (29th August 2018) - Aluzaite, Kristina; Tewhaiti-Smith, Jordan; Fraser, Margaret; Johnson, Steve; Glen, Elizabeth; Beck, Allison; Smith, Barbara; Dummer, Jack; Schultz, Michael
Abstract : Hepatitis C virus (HCV) and B virus (HBV) infections are highly prevalent, with a high percentage of undiagnosed cases. Knowledge of HCV and its modes of transmission are essential for disease prevention and management. We studied a high-risk New Zealand gang population on viral hepatitis prevalence, their level of knowledge and the liver health risk factors in a community setting. Participants completed demographic, risk factor and knowledge questionnaires in three health meetings in New Zealand. Participants' blood samples were tested for HBV, HCV, biochemical indicators of liver disease. Liver fibrosis levels were assessed using a Fibroscan ® device. We studied 52 adult Mongrel Mob members, affiliates and whānau (extended family) throughout New Zealand. We identified no HCV and two HBV cases, confirmed high-risk factor levels and poor associated knowledge, with a significant association between lack of knowledge and presence of specific risk factors. We successfully conducted a community-focused, high-risk, hard-to-reach gang population study, and found a link between lack of knowledge and risk factors for HCV infection. This study provided first-of-its-kind data on viral hepatitis in a gang population and demonstrated the need for educational screening programmes to aid early HCV detection, prevention and treatment.